Hubungan Gaya Belajar dengan Hasil Belajar IPA Siswa - Ayu Sukmawati; Ahmad Harjono; Ida Ermiana (Journal of Classroom Action Research, 2022)
This study aims to determine whether or not there is a relationship between learning styles and science learning outcomes for fourth-grade students at SDN Gugus 2, Sape District, for the 2019/2020 academic year. This research is a quantitative descriptive study with Ex Post Facto research techniques. The population in this study was 152 students consisting of 6 elementary schools in Cluster 2 Shape. The sample was determined using a probability sampling technique, namely proportionate stratified random sampling so that 110 students were obtained. Data collection techniques were used in this study, namely questionnaires and documentation. Data analysis to test the hypothesis with the Pearson Product Moment correlation test. The results showed that r arithmetic was 0.373 and r table was 0.618 > r table, it can be concluded that Ha is accepted and H0 is rejected. This means that there is a relationship between learning styles and science learning outcomes for fourth-grade students at SDN Cluster 2, Sape District, for the 2019/2020 Academic Year.